2007
DOI: 10.1007/s11104-007-9263-z
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based manipulation of nitrification in soil: a new approach to managing N loss?

Abstract: Much work has gone into the management of nitrification through applications of chemicals known to inhibit enzyme function in nitrifiers with indifferent outcomes when tested in the field. Much less attention has been focused on the capacity of plants to modify nitrification in situ. Subbarao and coworkers in a series of neat and elegant studies have confirmed that a tropical grass species, Brachiaria humidicola, produces chemicals that inhibit nitrification in soil. Critical to the work was the use of a Nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…The peaks observed (m/z, %) were 334 (M ϩ , 17), 291 (9), 245 (5), 227 (5), 199 (11), 149 (21), 137 (100), 136 (75), 121 (47), and 107 (22) (Fig. S3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks observed (m/z, %) were 334 (M ϩ , 17), 291 (9), 245 (5), 227 (5), 199 (11), 149 (21), 137 (100), 136 (75), 121 (47), and 107 (22) (Fig. S3).…”
Section: Methodsmentioning
confidence: 99%
“…Since the early 1960s, some tropical grasses have been suspected of having the capacity to inhibit nitrification (18)(19)(20)(21). However, this concept remained controversial due to the lack of direct evidence showing such inhibitory effects or the identification of specific inhibitors (22).…”
mentioning
confidence: 99%
“…Strategies to suppress nitrification after N fertilization could result in higher uptake of N in the form of NH 4 + by crops and might be additionally beneficial for plants preferring + (Boudsocq et al 2012), while reducing N losses to the environment. Synthetic nitrification inhibitors (SNIs) like nitrapyrin, 3,4-dimethylpyrazole phosphate (DMPP) and dicyandiamide (DCD) were shown to inhibit the activity of soil nitrifiers, but persistence of their effectiveness depends strongly on environmental factors (Zerulla et al 2001;Fillery 2007;Ruser and Schulz 2015). In addition, prices for SNIs are beyond the reach of smallholders that manage low input systems in tropical and subtropical regions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Lata et al (2004) demonstrated that nitrification can be suppressed or stimulated depending on the ecotype of Hypparhenia diplandra. Inhibition of nitrification can play a role in the functioning of these nutrient-poor grassland systems to control N losses (Lata et al 2004;Fillery 2007;Phillipot et al 2009). …”
Section: Discussionmentioning
confidence: 99%